The Existence of Tanjakas a Cultural Heritage That Must Be Preserved - Amalia, Tita; Putri, Khovivah Ananda; Syarifuddin, Syarifuddin; Supriyanto, Supriyanto (Local Wisdom Jurnal Ilmiah Kajian Kearifan Lokal, 2022)
Cultural diversity inherited from every previous generation create what is often called a local wisdom which in itself gives the area a unique socio-cultural identity. This cannot be any truer with Palembang with its many cultural wealth, one of which is a form of headdress or headband called tanjak. This study aims at investigating the existence of this culture from how it first got into the people of Palembang to today where even the government of the city has a mandate of making it an obligatory uniform for city officials on Fridays. to carry this investigation out, this study uses descriptive qualitative method. The data to be analysed come from both personal interviews (with experts on the matter) and literature or documentation studies. Initial results show that the move the government had taken was for the purpose of continuing to preserve and futher develop tanjak as a part of Palembang’s cultural wealth, as well as to educate the people regarding the needs to guard and preserver their local wisdom.